Розрахунок на міцність парогенератору для АЕС малої потужності - Кравченко, Володимир Петрович; Лимаренко, Олександр Михайлович; Чжоу, Сяолун; Хромий, Кіріл Олексійович; Бучка, Єгор Володимирович (Національний технічний університет "Харківський політехнічний інститут", 2021)
Зараз у світі спостерігається бурхливий розвиток АЕС малої потужності (АСМП). Більшість проектів розглядає реактори з водою під тиском та, відповідно, з парогенератором (ПГ). Україна має розвинену машинобудівну базу, яка може використовуватися для виготовлення обладнання для АСМП. В представленій роботі розглянуто розрахунок на міцність елементів прямоточного ПГ з циліндричними змієвиками, який є найбільш представницьким з усіх розглянутих проектів у матеріалах МАГАТЕ. Розроблено методику конструкційного розрахунку та розрахунку на міцність ПГ. Розроблено математичну модель, що включає розрахунок на міцність елементів ПГ аналітичним засобом за допомогою нормативної літератури та моделювання за допомогою програмного коду ANSYS. До вказаних елементів відносяться елементи корпусу (циліндрична частина, фланець, днище та кришка), патрубок теплоносія, теплообмінні трубки. Зіставлення результатів, отриманих двома методами, показало їх схожість та, відповідно, вірність результатів.

Today, the world oversees an explosive development of the nuclear power stations (NPS) of a low power. Most projects deal with pressurized water reactors and as a matter of fact with steam generators (SG). Ukraine has a well-developed engineering industry backbone that can be used for the production of the equipment required for the nuclear power plants of a low power. This scientific paper delves into the computations of the strength of elements used for the monotube steam generator with cylindrical coils that is the most presentable of all the pro- jects in question in IAEA materials. Appropriate methods were developed to perform structural computations and steam generator strength computations. The mathematical model was developed that allows us to perform strength computations of the SG elements making use of the analytical method with reference to the Regulations and do simulations using the ANSYS software code. The specified elements include the body elements, in particular the cylindrical part, the flange, the bottom and the cover, including the heat carrier branch pipe and heat exchange tubes. The comparison of the data obtained by both methods showed their similarity and accordingly, the accuracy of the data that are indicative of the need for an increase in the wall thickness of the cylindrical part of the external branch pipe intended for the heat carrier. The body bottom strain for calculated dimensions exceeds the permissible value by 1.56 %. Since this value is 5 % lower than permissible values it is deemed that the strength condition is passed through. The simulation proved that the strength conditions are met for heat exchange tubes, for the body, the body cover, the body flange, the conical part of the external branch pipe intended for the heat carrier. Based on the analysis done, we would like to recommend performing strength computations using the normative method with the subsequent check out by the simulation using the computer code.
Steam generator strength computation for nuclear electric power plants of a low power
Keywords: ядерна енергетична установка; парогенератор; розрахунок на міцність; числове моделювання; nuclear power plant; steam generator; strength; numerical modeling